Fundamentals of Materials Science, Diffusion
Este conjunto de animaciones proporciona una introduccin̤ a los mecanismos y fuerzas impulsoras de la difusin̤. Comprende los siguientes elementos:How do atoms move between atomic sites?Simulation of one-dimensional random walkSimulation of two-dimensional random walkInterstitial and substitutional diffusionSimulation of Ficks first lawSimulation of Ficks second lawMicrostructural effects on diffusionEffect of microstructure on diffusion at various temperaturesEffect of temperature on diffusion